Empowerment and local government autonomy - Iglesias, Gabriel U. (1986)
The Philippine development program places much concern on the rural sector which is the largest segment of the population. For its effective implementation, the involvement of the rural populace in government-sponsored programs and projects is solicited through the community organizations (COs). Systematic depoliticization and suppression of the more radicalized groups were however resorted to during the Marcos era to perpetuate the powers of the rural elites. Contrarily, the Aquino government is empowering the organized sector of the community and the autonomous local government units to perform functions and responsibilities to enable them to become effcctive partners of the central government in nation-building despite the worsening economic condition as exemplified by cases of malnutrition and increasing poverty of the rural households. It is posited that people participation in government activities develops the interest and commitment needed for the successful realization of development goals.
Keywords: Local government; Community development; Community organization